2021
DOI: 10.3390/nu13061776
|View full text |Cite
|
Sign up to set email alerts
|

Association between Geriatric Nutritional Risk Index and Post-Stroke Cognitive Outcomes

Abstract: Background: It is not yet clear whether nutritional status is associated with post-stroke cognitive impairment (PSCI). We examined the geriatric nutritional risk index (GNRI) on the domain-specific cognitive outcomes 3 months after a stroke. Methods: A total of 344 patients with acute ischemic stroke were included for the analysis. The GNRI was calculated as 1.489 × serum albumin (g/L) + 41.7 × admission weight (kg)/ideal body weight (kg) and was dichotomized according to the prespecified cut-off points for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…A Japanese study of 540 stroke patients, with a mean age of 80 years, showed that a low GNRI (<92) at baseline and predicted poorer functional outcomes, as represented by the functional independence measure (FIM) gain [32]. Moreover, a recent Korean study, based on 344 patients with stroke (mean age: 62 years), indicated that malnutrition (GNRI < 98) at admission was associated with a higher risk of post-stroke cognitive impairment (OR = 2.04) and lower scores in the specific cognitive domains of executive/activation and language [22]. Compared to MNA and MUST, which require completing structured questionnaires, the GNRI is more convenient to achieve [18].…”
Section: Gnri As a Predictor For Stroke Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…A Japanese study of 540 stroke patients, with a mean age of 80 years, showed that a low GNRI (<92) at baseline and predicted poorer functional outcomes, as represented by the functional independence measure (FIM) gain [32]. Moreover, a recent Korean study, based on 344 patients with stroke (mean age: 62 years), indicated that malnutrition (GNRI < 98) at admission was associated with a higher risk of post-stroke cognitive impairment (OR = 2.04) and lower scores in the specific cognitive domains of executive/activation and language [22]. Compared to MNA and MUST, which require completing structured questionnaires, the GNRI is more convenient to achieve [18].…”
Section: Gnri As a Predictor For Stroke Outcomementioning
confidence: 99%
“…Recently, several studies have validated the predictive value of the GNRI for clinical outcomes in patients with malignant, heart, and renal diseases and stroke [8,12,20,21]. Lee et al (2021) reported that lower GNRI scores were associated with a higher risk of post-stroke cognitive impairment [22] and lower cognitive scores in the Korean version of the mini-mental status examination and executive/activation domain. After stroke onset, cognitive impairment was highly correlated with depression at the same time point [23].…”
Section: Introductionmentioning
confidence: 99%
“…This index can predict the complications induced by malnutrition as well (Cereda et al., 2009 ). Predictions of some diseases incidence and prognosis have been made through GNRI in earlier investigations, including postoperative survival rate of esophageal cancer (Kubo et al., 2019 ), postoperative complications of gastric cancer (Kushiyama et al., 2018 ), postoperative bleeding of the pancreas (Funamizu et al., 2020 ), mortality of heart failure (Li et al., 2021 ), the prognosis of coronavirus disease(COVID‐19) (Lidoriki et al., 2020 ; Recinella et al., 2020 ), and poststroke cognitive impairment (Lee et al., 2021 ). Besides, studies have also found that malnutrition can lead to complications such as decreased immunity and infection (Keusch, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Geriatric Nutritional Risk Index (GNRI) is a widelyaccepted objective scoring system to effectively and conveniently evaluate the nutritional status of geriatric patients, which is simply calculated by height, body weight, and serum albumin, three readily accessible indices [18]. Studies have proven that a lot of diseases or outcomes were signi cantly associated with GNRI, such as Post-Stroke Cognitive Outcomes, arrhythmia recurrence, heart failure, and frailty [19][20][21][22]. However, few studies have investigated whether GNRI is signi cantly and independently associated with invasive candidiasis.…”
Section: Introductionmentioning
confidence: 99%